(untitled) (Nigerian Journal of Technology, 2016)
In this work, the Fourier transform method has been applied to the determination of stresses induced by infinitely long line loads on semi-infinite homogeneous elastic soils. Airy’s stress functions of the Cartesian coordinates system were used to express the governing equations of plane strain elasticity for a semi-infinite homogeneous soil as a biharmonic problem. The fourth order partial differential equation was then solved by an exponential Fourier transform technique, with respect to the space valuable x where -¥£x£¥; and the resulting solutions made subject to the stress – boundary conditions. The stresses obtained were found to be exactly identical with solutions obtained by integrating Boussinesq’s solutions for a point load which are available in the technical literature. The stresses determined in the present study were also exactly identical with the Flamant’s solution for the same problem; obtained by assuming a stress function in terms of the cylindrical coordinates. http://dx.doi.org/10.4314/njt.v35i4.6